2018
DOI: 10.1177/1099636218759683
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission loss of sandwich plate with pyramidal truss cores

Abstract: This paper presents the theoretical model of sandwich plate with pyramidal truss cores to investigate the acoustic property of transmission loss. The two-dimensional periodic model is established based on the assumption that the trusses are regarded as Euler-Bernoulli beams. The fluid-structure interaction is considered by imposing velocity continuity condition at fluid-structure interfaces. The periodic governing equations are derived by using space harmonic expansions and the principle of virtual work. Meanw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Wang et al [65] conducted some experiments to validate their theoretical model on the STL of sandwich panels with pyramidal truss cores. The effects of truss stiffness, incident angles, elevation angles, face-sheet thickness and material properties on the STL of the pyramidal truss core were carefully studied.…”
Section: Sandwich Core Support Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [65] conducted some experiments to validate their theoretical model on the STL of sandwich panels with pyramidal truss cores. The effects of truss stiffness, incident angles, elevation angles, face-sheet thickness and material properties on the STL of the pyramidal truss core were carefully studied.…”
Section: Sandwich Core Support Structuresmentioning
confidence: 99%
“…In their results, the STL increased with increased Mach number along the downstream direction while it decreased along the upstream directions. In addition, the authors observed minimal shifts in the peaks and dips of the STL curves toward higher frequency during downstream event and toward lower frequency Wang et al [65] conducted some experiments to validate their theoretical model on the STL of sandwich panels with pyramidal truss cores. The effects of truss stiffness, incident angles, elevation angles, face-sheet thickness and material properties on the STL of the pyramidal truss core were carefully studied.…”
Section: Sandwich Core Support Structuresmentioning
confidence: 99%
“…Sound transmission loss (STL) of panels is one of important acoustic issues for investigators in the past decades. The most appealing structures for sound transmission are sandwich structures made of multiple layer panels and cores [118]. Sandwich panels can be designed to have low density, high stiffness-to-mass ratio, excellent mechanical and acoustic characteristics, and hence have been widely applied as soundproof concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. [1] and Wangand Ma [4] established the periodic model of sandwich panel with pyramidal truss cores in two dimensions to calculate STL. Tang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight functional sandwich structures have been stimulated by the desire for superior and controllable mechanical properties that are expected and vital for actual applications [16]. To date, X-type metallic lattice truss cores prepared with stainless steels [7,8], octet lattice truss samples made from titanium alloys [9], tetrahedral cellular structures fabricated from carbon-fiber composites [10], and C/SiC pyramidal lattice truss sandwich panels [11], have been fabricated and investigated.…”
Section: Introductionmentioning
confidence: 99%